2007
DOI: 10.1007/s00464-007-9644-7
|View full text |Cite
|
Sign up to set email alerts
|

Polyflex self-expanding, removable plastic stents: assessment of treatment efficacy and safety in a variety of benign and malignant conditions of the esophagus

Abstract: Self-expanding, removable plastic stents are easily and safely placed and removed from the esophagus. This has facilitated their use in the authors' institution for an increasing number of esophageal conditions. Further studies to help define their ultimate role in benign and malignant esophageal pathology are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 32 publications
1
47
0
3
Order By: Relevance
“…This stent is composed of a polyester mesh with a silicone covering and has the theoretical advantages compared with self-expanding metallic stents of being removable and decreased tissue ingrowth [9]. Two small studies from 2004 reported dysphagia improvement in over 70% of patients after Polyflex TM stent placement and removal [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…This stent is composed of a polyester mesh with a silicone covering and has the theoretical advantages compared with self-expanding metallic stents of being removable and decreased tissue ingrowth [9]. Two small studies from 2004 reported dysphagia improvement in over 70% of patients after Polyflex TM stent placement and removal [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…SEMS are collapsed and inserted via a delivery system, which facilitates placement, minimizes the need for dilation, and reduces the incidence of trauma and perforation during insertion [9]. Uncovered SEMS have been associated with tumor in-growth and mucosal hyperplasia [7,8,10,11].…”
mentioning
confidence: 99%
“…Some studies [24][25][26] concluded that stent placement has been shown to be an excellent treatment in patients with mediastinal abscess in GEAL, while others [27] revealed that certain problems might be associated with stent placement and removal: insufficient closure of the leaks, stent migration and development of strictures after stent removal, severe complications such as bleeding and food blockage, and hard removal because of the growth of granulation tissue. Han et al [7] treated the patients of mediastinal abscess with stent placement and nasaloesophagus drainage.…”
Section: Discussionmentioning
confidence: 99%